Variation in the VP1 Gene of Foot-And-Mouth Disease Virus Serotype a Associated with Epidemiological Characteristics of Outbreaks in the 2001 Epizootic in Argentina - Pérez, Andrés M.; Konig, Guido Alberto; Spath, Ernesto Juan; Thurmond, Mark C. (Sage Publishing, 2023)
A mixed binomial Bayesian regression model was used to quantify the relation between nucleotide differences in the VP1 gene of Foot-and-mouth disease virus (FMDV) serotype A, and epidemiologic characteristics of the outbreaks from which the viruses were obtained between January and December 2001 in Argentina. An increase in the probability of different nucleotides between isolates was associated with a longer time between isolation dates, a greater distance between isolation locations, an increase in the difference between attack rates, and an increase in the difference in outbreak durations. The farther apart the outbreak herds were in the southerly and easterly directions, the greater the difference in nucleotide changes. The model accurately predicted genetic distances of isolates obtained in 2001 compared with a 2002 isolate (P < 0.01), which suggested that the predictive modeling approach applied in the present study may be useful in understanding the epidemiology of evolution of FMDV and in forensic analysis of disease epidemics.